Rancang Bangun Alat Peredam Kebisingan Berbasis Variasi Ketebalan Busa Dakron dan Egg Tray Terhadap Penurunan Intensitas Kebisingan di Industri Farmasi Tahun 2023 - Gunawan, Sukmawati; Kahar; Karmini, Mimin (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Purified Water Ambien Loop System in the pharmaceutical industry operates continuously and generates high noise. Preliminary results of the noise of the pump engine is 92.4 dBA. The purpose of this study was to determine the design of a noise dampening device based on variations in the thickness of dacron foam and egg tray to reduce noise intensity in the pharmaceutical industry. This type of research is true experiment with a pretest-posttest research design without control. Noise data was obtained using a Sound Level Meter and the sample size used was 36 samples using a purposive sampling technique. Data were analyzed using the one way anova test. The average results of noise intensity measurements before and after being treated for artificial noise sources variation 1 is 92.32 dBA to 87.45 dBA, variation 2 is 92.38 dBA to 84.26 dBA, variation 3 is 92.40 dBA to 78.18 dBA. Variation 3 has the highest percentage decrease of 13.73% - 17.12%. The conclusion is that there are significant differences from each variation to reducing noise intensity and all variations are effective in reducing noise intensity, it is suggested that the industry can use a noise dampening device design using dacron foam and egg tray media and further research needs to carry out further research to determine the saturation period in the media noise silencer.